Charlie Bumpers vs. The Squeaking Skull - Harley, Bill, 1954- (Peachtree Publishers, 2014)
As Halloween nears, Charlie and Tommy hope to get out of taking their little sisters trick-or-treating and go by themselves to Alex's upscale neighborhood instead, then attend a sleepover at Alex's house, but when Charlie learns that partygoers will be watching a very scary horror movie he panics.